Isolation, NMR and Mass Characterization of Ducose - A Novel Tetrasaccharide from Goat Milk - Singh, Pushpraj (Asian Journal of Pharmaceutical Research and Development, 2024)
Milk is an excellent source of all the necessary nutrients in the proper proportions. Besides the other regular constituents it has oligosaccharides in it which are indigestible by the infant yet are consumed by the microbial populations in the developing intestine. These oligosaccharides are believed to facilitate enrichment of a healthy infant gastrointestinal micro biota, often associated with bifidobacteria. Goat milk is a rich source of oligosaccharides that have enormous biological activities such as anti-bacterial, immunological, anti-inflammatory, hypoallergenic and therapeutic properties. It is used against tuberculosis in folk medicine and also helps in the enhancement of platelet count during dengue fever. Goat milk oligosaccharides have anti-inflammatory properties and are involved in the repairing process after a dextran sodium sulphate-induced colitis. Keeping in mind the biological importance of goat milk and the role of oligosaccharides, in the present studies, goat milk was analyzed for its oligosaccharide content which led to the isolation of a novel tetrasaccharide, ducose, C28H48O21N2. The structure of the isolated oligosaccharide was elucidated by chemical transformation, chemical degradation, 1H, 13C, 2D-NMR (COSY, TOCSY, HMBC and HSQC) and mass spectrometry as under. The geometry of compound ducose was optimized by B3LYP method and 6-31 G (d,p) basis set.